Święty Witold Pilecki wobec bezczelnego Tadeusza „Kosa” Kościuszki. Medialne dyskusje o filmach Kos i Raport Pileckiego z perspektywy politycznej i artystycznej recepcji - Kurpiewski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The article describes media discussions about the films Scarborn (2023) by Paweł Maślona and Pilecki’s Report (2023) by Krzysztof Łukaszewicz. A review of the reception of both films is used to illustrate several reception threads of contemporary biographical and historical cinema, with an emphasis on the political and artistic disputes taking place in discussions about films devoted to the heroes of the Polish past – Tadeusz Kościuszko (1746–1817) and Witold Pilecki (1901–1948).